Going the Distance by Going Green: DLSU’s Transportation System pre-, during, and post-pandemic - Onesimo O., Uy Arnel (Universitas Diponegoro, 2022)
sustainable operations agenda. Guided by this agenda, we formed partnerships to operationalize a greener transportation system. One of our initiatives is to partner with an electromechanical solutions provider in operationalizing our zero-emission vehicle (ZEV) policy with the use of electronic vehicles in our shuttle services before the pandemic. To reduce the number of private vehicles on campus, we also partnered with a bus company to provide a point-to-point service for our community members. During the pandemic, we continued to develop facilities and programs to encourage the use of bicycles by our community post-pandemic. With this, we look forward to further reducing the number of private vehicles on campus and the need to provide additional parking spaces. Keyword: Zero Emission Vehicles (ZEV), Shuttle services, Bicycles